Assisted performance – a pragmatic conception of online learning - Ab. Jalil, Habibah; McFarlane, Angela; Ismail, Ismi Arif; Rahman, Fadzilah (2008)
This paper proposes a novel theoretical perspective on the nature of online learning. Taking a socio-cultural perspective, an argument is offered for the theorisation of peer to peer learning as a variety of ‘assisted performance’. Using this theoretical lens, a case study is then offered which uses this model to frame an analysis of the nature and occurrences of online exchanges between students, and with tutors. The case study looks at two years of online discussion in a Master’s programme in a United Kingdom university. The results suggest that looking for examples of assisted performance in the online exchanges can offer insights into the learning that can take place in online discussion and offers one way of recognising meaningful online interaction, and therefore point to ways of promoting such exchanges.